Exploring Neurofilament Light Chain and Exosomes in the Genetic Forms of Frontotemporal Dementia - Zanardini, Roberta; Saraceno, Claudia; Benussi, Luisa; Squitti, Rosanna; Ghidoni, Roberta (Frontiers in Neuroscience, 2022)
Differential diagnosis of neurological disorders and their subtype classification are challenging without specific biomarkers. Genetic forms of these disorders, typified by an autosomal dominant family history, could offer a window to identify potential biomarkers by exploring the presymptomatic stages of the disease. Frontotemporal dementia (FTD) is the second cause of dementia with an age of onset < 65, and its most common mutations are in GRN, C9orf72 and MAPT genes. Several studies have demonstrated that the main proteins involved in FTD pathogenesis can be secreted in exosomes, a specific subtype of extracellular vesicles able to transfer biomolecules between cells avoiding cell-to-cell contact. Neurofilament light chain (NfL) levels in central nervous system have been advocated as biomarkers of axonal injury. NfL concentrations have been found increased in FTD and have been related to disease severity and prognosis. Little information on the relationship between NfL and exosomes in FTD has been collected, deriving mainly from traumatic brain injury. Current review deals with this matter in the attempt to provide an updated discussion of the role of NfL and exosomes as biomarkers of genetic forms of FTD.